Science dissemination and media criticism on the Nunca vi 1 cientista YouTube channel (RuMoRes, 2023)
This study aims to discuss new ways of presenting science problems and solutions in audiovisual content for a wide audience and analyze how this content circulates on YouTube based on the case of Nunca vi 1 Cientista, a channel with 200 thousand subscribers. We aimed to evaluate how the audiovisual content of scientific dissemination on YouTube differs from other consolidated proposals in traditional media within a media criticism approach that projects the expansion of TV narratives to other languages and devices. For this, we chose three episodes from the channel on the same theme and studied their central characteristics, such as the communicators’ language and performance. We also mapped aspects of their circulation based on their audience’s comments. We conclude that these new products break with more formal models of communication (such as journalistic content), provide authentic language and exchanges with their audience, and offer a critical approach in an accessible and dynamic way.